Biofuel in Thailand in the context of ASEAN economic community : analysis of stakeholders' perception, market and economic impact - Anuman Chanthawong; Dhakal, Shobhakar; Salam, Abdul P.; Juthathip Jongwanich; Kuwornu, John K.M.; HM King HRD Project; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
Amidst the growing concerns over fossil fuel-based energy systems and energy security, interest in biofuels and their development has intensified in recent years. Global production and trade in biofuels expanded rapidly from around 2004. Thailand is Southeast Asia's largest promoter of biofuels. Although Thailand promotes the use of biofuels, it has not yet achieved its policy targets. The key instruments used to promote production and consumption are mandatory blending targets, tax exemptions and subsidies. Biofuels positively contribute to energy security by reducing dependence upon imported fossil fuels and saving foreign exchange. Furthermore, it can improve the agricultural development by offering better prices, creating new jobs and mitigating greenhouse gas emissions by replacing fossil fuels. Therefore, the main objective of this study is analysis of biofuelpromotionin Thailand in the context of ASEAN Economic Community in terms of stakeholders{u2019} perception, market and economic impact. This study has four specific objectives: The first objective of the study is toanalyze the liquid biofuels development in Southeast Asiaand stakeholders' perceptions on challenges and opportunities for biodiesel and bioethanol policy development in Thailand. We used mix research methods (quantitative and qualitative methods). The analysis ofliquid biofuels development in Southeast Asian Countries was done by using qualitative methods which use meta-analysis. We used secondary data from 2000 to 2015. Meanwhile, stakeholders' perceptions on challenges and opportunities for biodiesel and bioethanol policy development in Thailand focuses on the first generation biofuel development in Thailand and examines the perceptions of seven stakeholder groups to guide further policy development. These stakeholders are feedstock producers, biofuel producers, government agencies, car manufacturers, oil companies, non-profit organizations and end users. It combines a Strengths, Weakness, Opportunities and Threats (SWOT) framework with an Analytical Hierarchy Process (AHP) framework and a TOWS Matrix to analyze stakeholders{u2019} perceptions to propose priorities for policy development. The second objective of this study is to analyze thesupply and demand of biofuels in the fuel market of Thailandwhichused the quantitative method by developing a theoretical model based on simultaneous equations, using Two Stage Least Square (2SLS) and Three Stage Least Square (3SLS) approaches compared with Artificial neural network (ANNs). Quarterly data were collected from 2007 to 2013:2.The third objective is todevelop multi-sectors, single-region computable general equilibrium framework of Thailand that focuses on biofuel policy analysis by developing Thailand Social Accounting Matrix (SAM) into 52 sectors which consist of 15 energy sectors and 37 non energy sectors. This model was used to analyze the impact of subsidy and taxation related to biofuels policies onthe economy of Thailand. The fourth and the last objective is to analyze theimpact of subsidy and taxation related to biofuels policies on the economy of Thailand using econometric estimation to develop a recursive dynamic computable general equilibrium model in order to analyze the impacts of biofuel policies on the economic social and energy factors of Thailand. This study carried out several simulations on two sets of issues: (1) policy of increasing excise taxthat consists of 12 scenarios such as increasing excise tax on oil products higher than biofuel products from 10 % to 40 %, and (2) policy of increasing subsidy on biofuels consisting of four scenarios by subsidizing at 10% to 40%. The results of liquid biofuels development in Southeast Asian Countries show that bioethanol and biodiesel in Southeast Asia are supplied to its domestic and regional market as well as exported to other countries in Asia and Europe of about 11 % and 38 % of the total production, respectively. The Southeast Asian biofuel market must focuson the regional context since ASEAN Economic Community in 2015 is expected to enhance the market integration. Thailand plays a key role in feedstock supply, production, domestic consumption and export of bioethanol in the region. Malaysia and Indonesia are major players in the biodiesel export market, but high domestic demand in the Philippines results in import dependency for bioethanol. The findings show that Thailand has a comprehensive set ofpolicies including ambitious national biofuels targets supported by fixing the price-floor for buying from farmers, mandatory blending, and demand side subsidies, while the policies in other countries are less comprehensive with targeting only certain specific aspects.
This analysis also shows that market linkages within Southeast Asian countries for bioethanol and biodiesel are generally unconstrained by the domestic market protection related to trade barriers except for biodiesel in Thailand. The five policies with high priority for development of biofuel in Thailand which was suggested by stakeholders{u2019} perceptions are: 1) promoting biofuel production and use in the long term through government policies, 2) revising government regulations to allow sale ofbiofuel products to other domestic industries while keeping retail prices of blended biofuels below those of regular ethanol and biodiesel, 3) improving farm management and promoting contract farming, 4)expanding cultivation areas and yield without affecting food production and environmental sustainability, and 5) balancing biofuel feedstock use between the food and energy industries.Moreover, for the long-term, factors that affect the supply and demand for biofuels (bioethanol and biodiesel) in Thailand can be identified by developing a theoretical model based on simultaneous equations. Amongst many factors, this study found three major factors affecting the long-term demand for biofuels: the price of biofuels, the real gross domestic product and the number of vehicles. On the other hand, the long-run supply of biodiesel and bioethanol was influenced by the gross domestic product, the cost of substitution using biofuel (i.e., price of gasoline 95 compared to blended gasoline) and the price of biodiesel. These findings have important policy implications forthe government plans for biofuel development. It suggests that maintaining the price difference between gasoline and gasohol (blended gasoline) and a greater penetration of biofuel vehicles in fleet would be important policies for biofuel consumption. On the biofuel supply side, results indicate that policies to compensate the biofuel producers for prices and reducing cost of biofuel production are important.Regarding the impact of subsidy and taxation related to biofuels policies on the economy of Thailand (used as a base case), this study found that Thailand will gain in economic, social, energy and technology factors when subsidy and taxation on biofuel are implemented. For the taxation policy, if theprices of oil and biofuels increase as a result of increasing excise tax, Thailand will gain in terms of GDP and welfare. Thus, increasing excise tax on oil and biofuel products at the same rate (40%) would result in GDP growth by 4.5% (29.8 trillion baht) and welfare (11.5%) as compared with the base case. However, this policy would have significant negative impacts on biofuel demand. On the other hand, increasing excise tax on oil higher than biofuel by 40 % would lead to increased GDP growth by 4.2 % (29.7 trillion baht), and welfare by 11.9%. This policy can promote biofuel products in Thailand. Thus, increasing excise tax leads to rising prices which would be paid by consumers relative to the initial equilibrium, while at the same time consumers earn more income from primary factors (especially increase in returns to labor). Income transfer raises household income. In general, income effect outweighs the consumption effect for most households, leading to higher welfare effect for most of households. Under the subsidy policy scenarios, increasing level of subsidy on biofuel products would have positive impacts on GDP and welfare. The biofuel subsidy policy has direct effects on agriculture sector through feedstock used (demanded). Under the subsidy policy scenarios, the industrial sector impacts highly on GDP, consistent with the fact that the strength of the economy of developed countries is based on industrial sector. The results show that increasing subsidy on biofuel at different levels would yield the same effects on GDP and welfare (i.e. GDP would increase by 1.6% (29 trillion baht) and welfare would increase by 3.6 %, under all subsidy scenarios (10%, 20%, 30%, 40%) as compared with the base case). This indicates that, the government could subsidize biofuel only 10% for promoting biofuel demand in Thailand and savegovernment expenditure. Biofuel development in Thailand,in the context of ASEAN economic community,could be developedin the entire supply chain of the biofuelsindustry startingfrom feedstock producers, biofuel producers, petroleum producers,vehicle producers and consumersin both the demand and supplyside. For demand side, the potential policy is promoting biofuel in long term through thefiscal policies,especially,taxation and subsidy. Moreover, the government could create awareness in the long-term.Atthe same time, for supply side policies, the government could be increasing supply of biofuel by improving farm management and expanding the cultivation area without affecting areas for food production and other sustainability concerns, increasing the infrastructure such as number of bioethanol stations, providing financial incentives to promotetheinvestment and production of biofuels in the entire supply chain of the biofuelindustry.The suggested policiescan be used to develop plans to assist Thailand to achieve social and economic sustainable development goals and to improve food and energy security.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Energy, School of Environment, Resources and Development
Thesis (Ph.D.) - Asian Institute of Technology, 2016
Keywords: Biomass energy; Alcohol as fuel; Biomass energy -- Thailand